2022
DOI: 10.2196/34121
|View full text |Cite
|
Sign up to set email alerts
|

Translating Promoting Factors and Behavior Change Principles Into a Blended and Technology-Supported Intervention to Stimulate Physical Activity in Children With Asthma (Foxfit): Design Study

Abstract: Background Children with asthma can decrease the impact of their disease by improving their physical activity (PA). However, health care providers lack interventions for children with asthma that effectively increase their PA levels and achieve behavior change. A technology-supported approach can positively influence PA and physical functioning in children. Objective The aims of this study were to develop a technology-supported intervention that facilit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 91 publications
(138 reference statements)
0
4
0
Order By: Relevance
“…In addition, the implementation of health promotion- and technology-supported approaches among asthmatic children clarified that education and intervention yielded more positive outcomes. 60 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the implementation of health promotion- and technology-supported approaches among asthmatic children clarified that education and intervention yielded more positive outcomes. 60 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, the implementation of health promotion-and technologysupported approaches among asthmatic children clarified that education and intervention yielded more positive outcomes. 60 The study could not identify a change in the general quality of life of the participants who received the manual only. Most participants in all three groups were smokers and alcohol drinkers, which was attributed to asthma symptoms.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…They have also emphasized the importance of mindfulness [ 33 , 36 ], goal setting, and support for tracking their progress [ 37 ] in overcoming obstacles during behavior changes. Previous research has suggested that providing step-by-step plans and personalized advice [ 38 ] and gamification [ 39 , 40 ] can also influence dietary and exercise habits, making them important factors for behavior change. The existing literature on behavior change using mobile health apps, along with the cocreation approach, can provide valuable insights into the features of mobile health apps that support healthy eating and physical activity.…”
Section: Introductionmentioning
confidence: 99%